Adapting Mindfulness‐Based Cognitive Therapy for Perinatal Depression to Improve Access and Appeal of Preventive Care. (17th December 2022) - Tilden, Ellen L.; Holmes, Leah R.; Vasquez Guzman, Cirila Estela; Orzech, Catherine Polan; Seghete, Kristen Mackiewicz; Eyo, Veronica; Supahan, Nisha; Rogers, Ginger R.; Caughey, Aaron B.; Starr, David; DiPietro, Jennifer L.; Fisher, Philip A.; et al.
Abstract: Existing and emerging evidence indicates that perinatal depression is a key contributor to preventable morbidity and mortality during and after childbearing. Despite this, there are few effective options for prevention and treatment that are readily accessible for and appealing to pregnant people. Aspects of routine health care systems contribute to this situation. Furthermore, societal and health care systems factors create additional barriers for people of color, people living in rural regions, and people living in poverty. Our interprofessional team of perinatal care providers, mental health providers, community partners, health services scientists, health equity scientists, and business leaders developed and are piloting a perinatal mental health preventive intervention designed to increase access and appeal of a program incorporating mindfulness cognitive behavioral therapy with proven efficacy in preventing perinatal depression. In this article, we briefly summarize key systems barriers to delivering preventive care for perinatal depression in standard prenatal care clinics. We then describe Mindfulness‐Based Cognitive Therapy for Perinatal Depression and outline our adaptation of this intervention, Center M. Finally, we identify next steps, challenges, and opportunities for this recent innovation.